2017
DOI: 10.3748/wjg.v23.i34.6231
|View full text |Cite
|
Sign up to set email alerts
|

Changes of Ghrelin/GOAT axis and mTOR pathway in the hypothalamus after sleeve gastrectomy in obese type-2 diabetes rats

Abstract: AIMTo examine the changes of the ghrelin/ghrelin O-acyltransferase (GOAT) axis and the mammalian target of rapamycin (mTOR) pathway in the hypothalamus after sleeve gastrectomy.METHODSA total of 30 obese type-2 diabetes Sprague-Dawley (SD) rats, 6 wk of age, fed with high-sugar and high-fat fodder for 2 mo plus intraperitoneal injection of streptozotocin were randomly divided into three groups: non-operation group (S0 group, n = 10), sham operation group (Sh group, n = 10) and sleeve gastrectomy group (SG grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 40 publications
(46 reference statements)
1
2
0
1
Order By: Relevance
“…Additionally, consistent with previously published data [21], severe impairments in liver metabolic function and lipid metabolism were observed in obese rats, which were significantly alleviated by SG. Indeed, the protective effects of SG against obesity have been reported in several studies [22][23][24], Endocrine Journal Advance Publication further confirming our findings in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Additionally, consistent with previously published data [21], severe impairments in liver metabolic function and lipid metabolism were observed in obese rats, which were significantly alleviated by SG. Indeed, the protective effects of SG against obesity have been reported in several studies [22][23][24], Endocrine Journal Advance Publication further confirming our findings in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In an experimental obese T2D rat model, a previous study found that the downregulation of ghrelin and activation of the hypothalamic mTOR pathway could produce an opposite effect on food intake after SG surgery. In addition, activation of the mTOR pathway accounted for increased NPY levels after SG [29]. Previous studies found that the nervous system, like the vagus nerve, is involved in the regulation of reduced appetite and food intake after the SG procedure; the gut-brain axis may play a vital regulatory role [30].…”
Section: Reduced Food Intakementioning
confidence: 94%
“…Для удобства дальнейших манипуляций под заднюю стенку желудка подкладывается сложенная в несколько раз салфетка. Операция ПРЖ заключается в удалении значительной части желудка (около 70%) с формированием из оставшейся части узкой трубки [23].…”
Section: продольная резекция желудка (прж)unclassified